A Rare Cause of Primary Aortoenteric Fistula: Streptococcus parasanguinis Aortitis - Fredy Nehme; Kyle Rowe; Cyrus Munguti; Imad Nassif (Case Reports in Gastrointestinal Medicine)
Primary aortoenteric fistula is a rare cause of upper gastrointestinal bleed but can lead to significant mortality if the diagnosis is delayed. Aortitis, characterized by inflammation of the aortic wall, is a rare cause of aortoenteric fistula. We present a case report of a 72-year-old male patient with infectious aortoenteric fistula secondary to Streptococcus parasanguinis, along with a review of the literature. This case demonstrates the importance of early diagnosis and aggressive surgical treatment of aortoenteric fistulae and recognizing infectious aortitis as a potential etiology.